THE APPLICATION OF THE ROLE PLAYING METHOD TO IMPROVE STUDENTS' SPEAKING SKILLS IN THE THEME AREA WHERE I LIVE CLASS IV : APPLICATION OF THE ROLE PLAYING METHOD TO IMPROVE STUDENTS' SPEAKING SKILLS - Iskandar, Karmila; Malae, Nurhalisa; Pateda, Lamsike (STIT Pringsewu, 2024)
This research aims to describe the improvement of students' speaking skills in the theme of the Region Where I Live Class IV at SDN 1 Busisingo, Sangkub District, North Bolaang Mongondow Regency by applying the Role Playing method. The Role Playing method is expected to improve students' speaking skills. This research method uses classroom action research (PTK) which was carried out in class IV at SDN 1 Busisingo. The subjects of this research were all class IV students with a total of 15 students. The treatment given to research subjects was to improve students' speaking skills in thematic learning in the area where I live using the Role Playing method. The results of this research show that the use of the Role Playing method can improve students' speaking skills. This increase can be seen from the assessment of the results of the theme 8 test, namely 27% after being applied to the posttest in cycle I, the average score was 40% and in cycle II the average score increased to 87%. Thus it can be concluded that the application of the Role Playing method is valid and can improve the speaking skills of class IV students at SDN 1 Busisingo.